Determinasi Underpricing Saham Perusahaan Non Keuangan yang Melakukan IPO di Bursa Efek Indonesia - Nurlela Nurlela; Maulida Putri Asri (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
This study aims to see the effect of Debt to Equity Ratio, Return On Equity, Firm Size, Rupiah Exchange Rate (Exchange Rate), Underwriter's Reputation, and Auditor's Reputation on Stock Underpricing at the time of Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) in 2011-2018. The research method in this research is descriptive statistical analysis and multiple linear regression test. The population in this study was 226 companies using purposive sampling technique, 128 companies were obtained as samples from 2011 to 2018. The type of data used was secondary data. Based on the results of the study, it shows that the Rupiah Exchange Rate (Exchange rate) has a significant positive effect on Underpricing, while the Underwriter's Reputation has a significant negative effect on Underpricing, meanwhile Return On Equity, Debt to Equity Ratio, and Auditor Reputation have no significant negative effect on Underpricing and Firm Size does not positive significant effect on underpricing. Keywords: Stock Underpricing, DER, ROE, Firm Size, Exchange Rate, Underwriter Reputation, and Auditor Reputation